Controlling of Water Flowrate in Pipe With Optimal Control - Eko Sarwono; Hendro Priyatman (Fakultas Teknik UM Pontianak, 2010)
Optimal control application gives more roles for performance improvement. One of control object is water flowrate in pipe with turbulence flow. This water flow kind could disturb process, measurement equipment, and so information from measuring not exactly measurable and observable. According that reason, control system the water flowrate are needed to decrease error from steady state condition. Comparing simulation result from system no control and with optimal control, can be concluded that optimal controller design could improve system performance, with decrease error, because all information about state could be measured and observed. Optimal controller design by simulation is better use with high speed Personal Computer (PC) and capability to process information. PC’s delay effect from low speed PC for data processing which represented by graphic could give unsatisfaction simulation result.Keywords: Flowrate, Optimal Control.